Formal study of sleep-disordered breathing in senior citizens: an AHI comparison - Kikuchi, Atsushi; Ikezono, Keiko; Nakashima, Tadashi; Sato, Kiminori (Stomato-pharyngology, 2012)
We examined the formal diagnosis of sleep-disordered breathing (SDB) in senior citizens, that is 301 subjects-213 men and 88 women-aged 65 and over. We then compared apnea hypopnea index (AHI), body mass index (BMI), and form feature by gender to that in subjects under age 65. Although “loosening” was increasingly seen among those 65 and older and severe AHI group, age and AHI were not correlated. In senior citizens' SDB, lower pharynx and “loosening” were increasing regardless of gender, suggesting the possibility of severe SDB. Although “loosening” was difficult to rate objectively, diagnosis is comparatively easy and was found to be useful in the screening of elder SDB.